Biological parameters of Bemisia tabaci (Gennadius) Biotype B (Hemiptera: Aleyrodidae) on Jatropha gossypiifolia, Commercial (Manihot esculenta) and wild cassava (Manihot flabellifolia and M. carthaginensis) (Euphorbiaceae) - Carabalí, A.; Bellotti, Anthony C.; Montoya Lerma, J. (Springer, 2010)
Bemisia tabaci (Gennadius) is one of the most important pests of cassava in Africa and several countries of Asia due to the damage caused by direct feeding, the excretion of honeydew, and its capacity as a vector of cassava mosaic geminivirus. There is a general consensus that B. tabaci is a complex of morphologically indistinguishable populations with different biotypes. In the Americas, the polyphagous biotype B does not appear to feed on cassava. Recent studies indicate that it is possible, however, for biotype B to gradually adapt to cassava using phylogenetically related hosts. Therefore, the possibility that some wild species of cassava constitute intermediate hosts in the adaptation process may lead to the establishment of biotype B on commercial varieties of Manihot esculenta. In here, we evaluated Jatropha gossypiifolia, two wild species of cassava (Manihot flabellifolia and M. carthaginensis) and a commercial cassava variety (MCol 2063) as hosts of biotype B. The highest oviposition rate (2.7 eggs /two days) occurred on M. esculenta, although the development time (44 d) was the longest when compared to M. carthaginensis and J. gossypiifolia. About 60% of the population could reproduce on the wild cassava species vs. 55% on J. gossypiifolia and 27.5% on the commercial variety. Our data suggest that J. gossypiifolia is a suitable host and the wild species M. carthaginensis can constitute a potential intermediate host in the adaptation of biotype B to commercial varieties of cassava.